Current and Perspective Approaches to the Treatment of Prolactinomas - Barabash, Nadiya; Tykhonova, Tetiana; Kanishcheva, Olena (Acta medica Lituanica, 2023)
Background: Along with the presence of the 2011 Endocrine Society Clinical Practice Guidelines and numerous large-scale studies on the treatment of hyperprolactinemia of different origin, there are some unresolved questions, ambiguous and sometimes contradictory points of view regarding the management of patients with prolactinomas. This overview is devoted to the analysis of the results of modern clinical studies and the approaches towards the management of hyperprolactinemia caused by prolactinoma. Materials and methods: A systematic research of the literature for the appropriate keywords published mainly for the last 10 years was done; also, a reference list of each selected article was analysed. We included to our review the articles reporting controversial issues or new data on the treatment of hyperprolactinemia. Results: The review describes various problems arising during the treatment of prolactinoma. The presence of primary and secondary dopamine agonist resistance in each case requires an individual approach, and sometimes may include the use of the antineoplastic agent temozolomide. The side effects of dopamine agonists are discussed, with quite rare ones, including valvulopathy, pathological psychological conditions and cerebrospinal rhinorrhea. The controversial issue of the duration and doses of the drug used to achieve a lasting effect in the treatment of prolactinomas is considered. There are some points connected with the frequency of relapses. Thus, recurrence is correlated to the duration of treatment with dopamine agonists, prolactin levels at diagnosis, and the initial tumor size. Metformin, somatostatin analogues, selective estrogen receptor modulators, tyrosine kinase inhibitors, inhibitors of the mammalian target of rapamycin, epidermal growth factor receptor antagonists are investigated nowadays as potential alternative methods of drug treatment of prolactinomas. Conclusion: Drug therapy with dopamine agonists makes it possible to achieve the desired results in the vast majority of patients. However, despite the proven safety of this group of medicines, the risk of side effects should still be taken into account. The therapy regimen should be determined by the clinical course of prolactinoma and the patient’s response to treatment. Other options of treatment should be considered in patients intolerant to medical therapy, with contraindication or resistance to dopamine agonists, in the case of a malignant tumor. The presence of refractory to any of the applied methods of treatment and aggressive prolactinomas leads to the search for new drugs.